Implementasi Undang-Undang Nomor 16 Tahun 2019 dalam Penanganan Permohonan Dispensasi Nikah di KUA Kecamatan Kaligesing - Nabilah, Wafa; Sudarmaji, Waluyo; Marzuki, Arifuat (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Law Number 16 of 2019 establishes the minimum age for marriage for both men and women at 19 years old. However, the practice of marriage dispensation still frequently occurs. The Office of Religious Affairs (KUA) of Kaligesing faces challenges in implementing this regulation, as it must balance national law with local traditions that still consider early marriage to be acceptable. This study aims to examine how Law Number 16 of 2019, which amends Law Number 1 of 1974, is implemented in handling marriage dispensation applications at the KUA of Kaligesing Subdistrict, Purworejo Regency. The research employs a qualitative approach with a case study design, based on data collected through field research as well as literature references. The findings indicate that the implementation of Law Number 16 of 2019 at the KUA of Kaligesing Subdistrict has been carried out effectively in both administrative and educational aspects. Nevertheless, social, cultural, and economic obstacles remain, leading to the continued occurrence of early marriages. A more holistic approach is needed through enhanced legal education, strengthening of religious and family values, and a reassessment of marriage dispensation policies to achieve the goal of child protection.